A Systematic Review of Technology Integration in Early Childhood Education - Yuyun Istiana; Mardi Widodo (Early Childhood Education Development and Studies (ECEDS), 2023)
This systematic review article provides an in-depth examination of the integration of technology in Early Childhood Education (ECE) within the specific context of Indonesia. It aims to analyse and synthesise existing studies that have explored the employment of technology in ECE, with a focus on significant findings, methodologies used, and challenges encountered. This review also seeks to identify and comprehend the obstacles Indonesia faces in the endeavour of integrating technology in ECE, covering issues such as technological divide, teacher quality and readiness, and the availability and condition of infrastructures. Furthermore, it attempts to investigate the opportunities present in harnessing technology to fortify ECE in Indonesia by considering the current trend of technology adoption in Indonesia and potential types of technology that could be incorporated in ECE. Based on these objectives, the review aspires to provide useful recommendations for policymakers, educational practitioners, and researchers in devising and implementing effective strategies for technology integration in ECE. The results of this comprehensive review reveal that, despite significant challenges, the potential and opportunities offered by technology for ECE are vast and need to be capitalised optimally. The paper underscores the necessity of a thorough understanding, holistic approach, adequate preparation, and commitment from all stakeholders in achieving successful integration of technology in ECE in Indonesia.